Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Kalkulus - Sumargiyani Sumargiyani; Indah Yusnia; Rahmi Nurhasanah; Bidayatun Nafi'ah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
Some students have difficulty solving math problems in the integral calculus course, one of the materials for the volume of rotating objects. The purpose of this research is to describe the types of errors made by students of class F Mathematics Education FKIP Ahmad Dahlan University and their causes in solving the volume of rotating objects in integral calculus courses in the Polya stage. This research is a quantitative quantitative research. The research subjects are one class with a total of 20 students. For interviews, 3 students were taken with the criteria of high, medium and low abilities. Collecting research data using test material, the volume of rotating objects and student interviews about the factors that cause mistakes made. The steps for solving the problem consist of four stages, namely: understanding the problem, planning for completion, implementing the plan, and examining the solutions obtained. From the results of the research on student errors based on Polya's stages: 1) understanding the problem 55.89%, planning for completion of 50.00%, errors in implementing planning 32.36%, and errors in re-checking the process and results 44.12%; 2) the causes of students making mistakes in solving integral calculus questions on the volume of rotating objects, namely students lacking mastery in drawing function graphs, students lacking in basic concepts and volume formulas for rotating objects, and students unable to analyze the questions given.